2018
DOI: 10.3892/ol.2018.8336
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑1266‑5P, miR‑185‑5P and miR‑30c‑2 in prostatic cancer tissue and cell lines

Abstract: Over the latest decade, the role of microRNAs (miRNAs/miRs) has received more attention. miRNAs are small non-coding RNAs that may serve a role as oncogenes or tumor suppressor genes. Certain miRNAs regulate the apoptosis pathway by influencing pro- or anti-apoptotic genes. We hypothesized that increases in the expression of B cell lymphoma 2 () and BCL2-like 1 () genes, which have been reported in various types of cancer tissues, may be due to the downregulation of certain miRNAs. The present study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In our study, low expression levels of miR-185-5p and miR-106a-5p or the high expression of miR-10b-5p were associated with a short survival. miR-185-5p has been already reported in the literature as a potential cancer biomarker for melanoma [38], prostate [39], and bladder cancer [14,40]. However, the expression rates of this miRNA are not consistent across studies, thus raising some issues about the possibility to clarify its complex molecular involvement in tumor progression, also considering the heterogeneity of tissues and cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, low expression levels of miR-185-5p and miR-106a-5p or the high expression of miR-10b-5p were associated with a short survival. miR-185-5p has been already reported in the literature as a potential cancer biomarker for melanoma [38], prostate [39], and bladder cancer [14,40]. However, the expression rates of this miRNA are not consistent across studies, thus raising some issues about the possibility to clarify its complex molecular involvement in tumor progression, also considering the heterogeneity of tissues and cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were validated in BM, such as TWIST1, GSTA5, and BCL2L1 [106]. Interestingly, BCL2L1 is regulated by miR-1266, miR-185, and miR-30c [60] in prostate cancer. TWIST1 is regulated by miR-151-3p in BC [61].…”
Section: Extravasationmentioning
confidence: 99%
“…18 At present, emerging evidence revealed that miRNAs could affect cellular responses to radiation and modulate the radiosensitivity of many cancers. 19 MiR-185-5p has been suggested to be dysregulated in many kinds of cancers, such as prostatic cancer, 20 hepatocellular carcinoma, 21 clear cell renal cell carcinoma. 22 Moreover, previous study suggested that miR-185-5p was expressed at a low level in BC cells.…”
Section: Introductionmentioning
confidence: 99%